Effectiveness of Using Mystery Motion Maps for Social Studies Learning as a Key to Building Collaboration for Social Sciences Students in class VIII-E at SMP Negeri 16 Malang - Muhammad Burhanudin Fadly; Nurul Ratnawati (JURNAL PENDIDIKAN IPS, 2025)
This research aims to investigate the effectiveness of using Mystery Motion Map Media for students who really understand interactive learning media, and build student collaboration in increasing the effectiveness of Social Sciences (IPS) learning at SMP 16 Malang schools. Social studies learning is often considered less interesting and relevant, so the integration of appropriate media and a collaborative approach is expected to overcome this challenge. This research examines how the use of various types of learning media, such as digital platforms, videos, and simulations, in the context of group activities, discussions, and joint projects, can influence the understanding of social studies concepts, student engagement, and the development of social skills. It is hoped that the research results can provide practical insight for educators in designing and implementing more effective and meaningful social studies learning through the use of media that is integrated with collaborative strategies. The implications of this research highlight the importance of creating an active, interactive, and student-centered learning environment to achieve optimal social studies learning outcomes.